Islamic Boarding Schools and Universities' Curriculum Management Based on Spiritual and Intellectual Mentality - Bahrur Rozi; Pujiono .; Maskud . (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The phenomenon of integrating Islamic boarding schools with universities is an exciting phenomenon to observe. This article discusses the curriculum development design for Islamic boarding schools and tertiary institutions in shaping female students' spiritual and intellectual intelligence. In this study, the authors used descriptive-critical research emphasizing the power of analysis of existing sources and data by relying on existing theories and concepts to be interpreted based on writings that lead to discussion. Based on the results of the study of primary sources, it can be concluded that student boarding schools create or design their curriculum based on curriculum management theory, starting from planning, organizing, actuating, and controlling/ evaluating. This is seen as necessary so that student boarding schools can maximally give their role to students in fostering their mental, spiritual and intellectual development.